Ceramic unguentaria from Scallabis (Santarém, Portugal) - de Sousa, Elisa; Margarida Arruda, Ana (Rei Cretariae Romanae Fautorum Acta, 2022)
Archaeological field work carried out in Alcáçova de Santarém (Portugal) during the last two decades of the 20th century have identified a significant amount of data concerning the site’s occupation during the Roman period. In this work, we present and analyze a particular type of archaeological materials associated to this phase, the ceramic unguentaria. This set is, so far, the largest uncovered in habitat settlements in the Portuguese territory (65 fragments – 30 individuals), encompassing the two main shapes of these vessels (fusiform and bulbous profiles), apparently imported from the Italic Peninsula, between the 2nd century BC and the first half of the 1st century AD.